The impact of corrective feedback on EFL learners’ acquisition of regular and irregular past simple forms: evidence from a Portuguese context using a picture description task - Ana Rita Faustino, (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2024)
Corrective Feedback (CF) is a common practice in the foreign language classroom and constitutes a topic of interest for both language teachers – who have to decide whether to correct their students, when and how – and for L2 researchers – who are interested in testing the efficacy of CF techniques in L2 acquisition. Conducted in a state school in Portugal, this quasi-experimental study investigated the effects of three CF strategies – recasts, prompts and explicit correction – and of no feedback on the acquisition of English regular and irregular past tense forms. 166 9th-grade Portuguese students (and their five teachers) took part in the study and were tested in a pretest-posttest design. Comparisons of group means using ANOVA revealed a significant effect for test time. Post-hoc analyses revealed that the Prompt group significantly outperformed both the Explicit Correction group and the Recast group in the production of regular past tense items and showed significant improvement between the Pretest and Posttest 2 in the use of irregular past tense.